Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Section: xi, 434 pages : illustrations, cartes ; 24 cm
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Prostitution et immigration des femmes latino-américaines en Espagne - Oso Casas, Laura (Cahiers du Genre, 2006)
L’objectif de cet article est de montrer qu’une bonne partie des femmes latino-américaines, contrairement à l’image souvent mise en avant de la femme objet de trafic, ont pris la décision de migrer en étant conscientes de l’activité qu’elles allaient pratiquer en Espagne. Cependant, bien qu’elles puissent opter volontairement pour le « travail » sexuel, devenant les principales pourvoyeuses économiques des foyers transnationaux (actrices de la migration, actrices économiques et du développement), elles sont prises dans plusieurs circuits qui contribuent à la reproduction des inégalités sociales. Ces circuits sont sous-tendus par l’articulation de plusieurs facteurs : la circulation des personnes, la mobilité des prostituées, la pression du foyer transnational, l’irrégularité juridique, ainsi que l’inégalité de genre.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du sud; amériques; approches et analyses; cours; discipline; espagne; europe; immigration; inégalités; migration; postmodernisme; premier cycle; prostitution; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

The transgender studies reader - Stryker, Susan; Whittle, Stephen (Routledge, 2006)
Although the term "transgender" itself has achieved familiarity only within the past decade, this authoritative collection of articles demonstrates that the study of behaviors, bodies, and subjective identities which contest common Eurocentric notions of gender has a history stretching back at least to the early 20th century. Transgender studies is the latest area of academic inquiry to grow out of the exciting nexus of queer theory, feminist studies, and the history of sexuality. Because transpeople challenge our most fundamental assumptions about the relationship between bodies, desire, and identity, the field is both fascinating and contentious. The Transgender Studies Reader puts between two covers fifty influential texts with new introductions by the editors that, taken together, document the evolution of transgender studies in the English-speaking world. By bringing together the voices and experience of transgender individuals, doctors, psychologists, and academically-based theorists, this volume will be a foundational text for the transgender community, transgender studies, and related queer theory.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; interdisciplinarité; occident; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques